Effective photocatalytic removal of different dye stuffs using green synthesized zinc oxide nanogranules. (June 2018) - Prasad, Anupama R.; Rugmini Ammal, P.; Joseph, Abraham
Graphical abstract: Highlights: Zinc oxide nanoparticles (ZnO-NPs) synthesized by a green strategy using lemon juice and ethylene glycol. Physicochemical studies confess the formation of hexagonal wurtzite ZnO nanaogranules with some honed faces. Direct band gap energy obtained for ZnO nano granules was 3.15 eV. ZnO nano granules act as good catalyst for the photo degradation of methylene blue, congo red, and rhodamine B under UV-light irradiation. Abstract: Zinc oxide nanoparticles (ZnO-NPs) obtained by a green synthetic strategy using lemon juice and ethylene glycol. The material was characterized using the techniques UV–vis spectroscopy, FTIR spectroscopy, X-ray diffraction analysis, FESEM, EDAX and HRTEM. Diffraction patterns and TEM micrographs confess the formation of hexagonal wurtzite ZnO nanaogranules with some honed faces and having an average size of 49.16 nm. The developed ZnO-NPs was tested for the photocatalytic degradation of Methylene Blue, Congo Red and Rhodamine B target dyes under UV irradiation and found to have remarkable activity.